Harapan Orangtua Terhadap Anak: Eksplorasi Pada Nilai Anak (Value Of Children) Dan Perilaku Pengasuhan - Haerani Nur; Eka Sufartianingsih Jafar (Universitas Negeri Makassar, 2023)
This study aims to explore why parents have certain expectations of their children, how these expectations then affect parenting behavior towards their children, and the value of children is found to be one of the concepts that can be used to explore parental expectations. This study uses a survey method, the researcher distributes a questionnaire with open-ended questions using a google form. Data were analyzed using open coding and axial coding. A total of 39 parents became respondents in this study. The results of data analysis found that in addition to economic values, psychological values, and social values, spiritual values were also found, depicted by the hope that by having children, someone prayed and became a form of piety. Spiritual values are the most dominant values, so taking time for children, getting used to discussions, building discipline, giving rules are the most mentioned themes that describe parenting behavior. The results of this study indicate the need for further research to explain how parenting behavior is if parents' expectations of their children are dominated by economic values, social values, or psychological values.